2016
DOI: 10.3390/rs8030165
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Inter-Calibration between Himawari-8 AHI and S-NPP VIIRS for the Solar Reflective Bands

Abstract: Abstract:The Advanced Himawari Imager (AHI) on-board Himawari-8, which was launched on 7 October 2014, is the first geostationary instrument housed with a solar diffuser to provide accurate onboard calibrated data for the visible and near-infrared (VNIR) bands. In this study, the Ray-matching and collocated Deep Convective Cloud (DCC) methods, both of which are based on incidently collocated homogeneous pairs between AHI and Suomi NPP (S-NPP) Visible Infrared Imaging Radiometer Suite (VIIRS), are used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…The stray light correction was found to reduce the fit offsets and gains for all considered channel pairs. Yu and Wu (2016) investigated the intercalibration between Advanced Himawari Imager (AHI) in a geostationary orbit and VIIRS. They found strong linear relationship between the paired bands.…”
Section: Introductionmentioning
confidence: 99%
“…The stray light correction was found to reduce the fit offsets and gains for all considered channel pairs. Yu and Wu (2016) investigated the intercalibration between Advanced Himawari Imager (AHI) in a geostationary orbit and VIIRS. They found strong linear relationship between the paired bands.…”
Section: Introductionmentioning
confidence: 99%
“…The Himawari-8 AHI and MODIS Terra/Aqua bias offset varied, with the green band showing −0.02 and the NIR (AHI B4, Terra/Aqua B2) band showing +0.03. A recent study by Yu and Wu also noted similar bias for TOA reflectance between Himawari-8 AHI and S-NPP VIIRS [6]. Diurnal cycles of meteorological variables and sun zenith/azimuth angle changes might be the main contributors to the bias between Himawari-8 AHI and MODIS SR. We used ray-matching screened pixels to remove the diurnal variability of aerosols and clouds in next section to further examine the possible discrepancy between Himawari-8 AHI and MODIS Terra/Aqua SR data.…”
Section: Evaluation Of Himawari-8 Ahi Sr Over Vegetation Sitesmentioning
confidence: 59%
“…We used the ray-matching method to select collocated pixel pairs from HM08_AHI12 and the reference MODIS data. The ray-matching method is a straightforward tool to match pixels from GEO and LEO sensors for comparison [6,29,30]. The method relies on precise spatially and view geometry collocated target pixels to reduce the atmosphere and BRDF impact.…”
Section: Ray-matching Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the varying spatial resolutions, they were averaged to a spatial distance of 2.0 km. Cao et al [27] reported that the absolute radiometric calibration accuracy of S-NPP/VIRS is less than 2% for CH1-CH6 and the calibration accuracy of this data and Himawari-8/AHI was reported to be within 6-8% of CH1-CH4 and CH6 except for CH5 (5%) [28]. …”
Section: Input Datamentioning
confidence: 99%